The Forearm Fracture Recovery in Children Evaluation (FORCE) trial: statistical and health economic analysis plan for an equivalence randomized controlled trial of treatment for torus fractures of the distal radius in children. (9th June 2020) - Knight, Ruth; Dritsaki, Melina; Mason, James; Perry, Daniel C.; Dutton, Susan J.
Abstract : Aims: Torus fractures of the distal radius are the most common fractures in children. The NICE non-complex fracture guidelines recently concluded that bandaging was probably the optimal treatment for these injuries. However, across the UK current treatment varies widely due to a lack of evidence underpinning the guidelines. The Forearm Fracture Recovery in Children Evaluation (FORCE) trial evaluates the effect of a soft bandage and immediate discharge compared with rigid immobilization. Methods: FORCE is a multicentre, parallel group randomized controlled equivalence trial. The primary outcome is the Wong-Baker FACES pain score at three days after randomization and the primary analysis of this outcome will use a multivariate linear regression model to compare the two groups. Secondary outcomes are measured at one and seven days, and three and six-weeks post-randomization and include the Patient Reported Outcome Measurement Information System (PROMIS) upper extremity limb score, EuroQoL EQ-5D-Y, analgesia use, school absence, complications, and healthcare resource use. The planned statistical and health economic analyses for this trial are described here. The FORCE trial protocol has been published separately. Conclusion: This paper provides details of the planned analyses for this trial, and will reduce the risks of outcome reporting bias and data driven results. Cite this article: Bone Joint Open 2020;1-6:205–213.